The Eucharistic Spirit: A Renewal Theology of the Lord’s Supper: Oleh Florian M. P. Simatupang - Layantara, Jessica Novia (Indonesian Journal of Theology, 2025)
A book review of The Eucharistic Spirit: A Renewal Theology of the Lord’s Supper